New approach to catalytic Co-W alloy electodeposition - Ved, M.; Shtefan, V.; Bairachnaya, T.; Sakhnenko, N. (Functional Materials, 2007)
The pulse electolysis parameters (current density amplitude, frequency and on/off time ratio of pulses, pause and pulse duration) influence on cobalt-tungsten alloy deposition has been revealed. The alloy electodeposition possibility using loluble anodes has been proved. Corrosive resistance and catalytic activity of obtained coating have been determined.